2021
DOI: 10.3390/molecules26133941
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Drug Nanocrystals for Film Formulations

Abstract: The aim of the study was to prepare indomethacin nanocrystal-loaded, 3D-printed, fast-dissolving oral polymeric film formulations. Nanocrystals were produced by the wet pearl milling technique, and 3D printing was performed by the semi-solid extrusion method. Hydroxypropyl methyl cellulose (HPMC) was the film-forming polymer, and glycerol the plasticizer. In-depth physicochemical characterization was made, including solid-state determination, particle size and size deviation analysis, film appearance evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Then, students’ performance can be comprehensively analyzed by factoring in multiple influencing factors. In turn, the evaluation results can be used to devise targeted teaching and learning strategies for each student ( Germini and Peltonen, 2021 ). As a result, Cinematography talents with comprehensive knowledge and quality can be cultivated ( Hassan, 2021 ).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Then, students’ performance can be comprehensively analyzed by factoring in multiple influencing factors. In turn, the evaluation results can be used to devise targeted teaching and learning strategies for each student ( Germini and Peltonen, 2021 ). As a result, Cinematography talents with comprehensive knowledge and quality can be cultivated ( Hassan, 2021 ).…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The method optimized that the effective mechanical film potentials were obtained at two concentrations of the polymer, 3.5% (w/w) and (2.85% (w/w), and the particle size of the drug nanocrystal was found to be 230 nm. Ultimately, the study concluded that drug nanocrystal 3D printing via oral polymeric film formulations is an effective method for instant drug release with high solubility [153].…”
Section: Cancer Drug Delivery/screening and 3d Printingmentioning
confidence: 99%
“…For instance, nanocrystals have been further developed by the utilisation of 3D printing to further develop the technology and derive increased utility. [99][100][101] Furthermore, the prospect of loading nanomaterials in nano-bers presents an additional opportunity for further manufacture. 102 These could be extrapolated to NCC for potential additive manufacturing.…”
Section: Additive Manufacturingmentioning
confidence: 99%